(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article discusses corruption risks related to the time limits for reviewing appeals of individuals and legal entities, the procedure for extending and shortening such time limits, as well as liability for violations of legislation on appeals, and examines ways to eliminate these risks. Official statistical data on the consideration of appeals by state bodies and organizations are presented. The article also highlights the prospective tasks envisaged in the field of handling appeals under the updated “Uzbekistan – 2030” Strategy. Certain problematic issues related to administrative and criminal liability for violations of legislation on appeals of individuals and legal entities are analyzed through a comparative legal approach. The scientific and theoretical views of legal scholars, as well as the experience of a number of foreign countries regarding the time limits for considering appeals, are examined, comparatively analyzed with national legislation, and relevant proposals are put forward.